Contributions to the morphology and histology of the reproductive system of Limacia clavigera Muller (1776) (Opisthobranchiata: Nudibranchiata) - Heyns, M.(Marise),1967- (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1989.